USP25 attenuates anti-GBM nephritis in mice by negative feedback regulation of Th17 cell differentiation - Ranran Xu; Fei Huang; Qingquan Liu; Yongman Lv; Liu Hu; Qian Zhang (Renal Failure)
Purpose This study aimed to elucidate the role of USP25 in a mouse model of anti-glomerular basement membrane glomerulonephritis (anti-GBM GN).Methods USP25-deficient anti-GBM GN mice were generated, and their nephritis progression was monitored. Naïve CD4+ T cells were isolated from spleen lymphocytes and stimulated to differentiate into Th1, Th2, and Th17 cells. This approach was used to investigate the impact of USP25 on CD4+ T lymphocyte differentiation in vitro. Furthermore, changes in USP25 expression were monitored during Th17 differentiation, both in vivo and in vitro.Results USP25−/− mice with anti-GBM GN exhibited accelerated renal function deterioration, increased infiltration of Th1 and Th17 cells, and elevated RORγt transcription. In vitro experiments demonstrated that USP25−/− CD4+ T lymphocytes had a higher proportion for Th17 cell differentiation and exhibited higher RORγt levels upon stimulation. Wild-type mice with anti-GBM GN showed higher USP25 levels compared to healthy mice, and a positive correlation was observed between USP25 levels and Th17 cell counts. Similar trends were observed in vitro.Conclusion USP25 plays a crucial role in mitigating renal histopathological and functional damage during anti-GBM GN in mice. This protective effect is primarily attributed to USP25’s ability to inhibit the differentiation of naïve CD4+ T cells into Th17 cells. The underlying mechanism may involve the downregulation of RORγt. Additionally, during increased inflammatory responses or Th17 cell differentiation, USP25 expression is activated, forming a negative feedback regulatory loop that attenuates immune activation.